Methanation of carbon dioxide on Ru/Al2O3 and Ni/Al2O3 catalysts at atmospheric pressure: Catalysts activation, behaviour and stability. (10th August 2015) - Garbarino, Gabriella; Bellotti, Daria; Riani, Paola; Magistri, Loredana; Busca, Guido
Abstract: The methanation of carbon dioxide has been studied over 3% Ru/Al2 O3 and 20% Ni/Al2 O3 commercial catalysts. Experiments have been performed in diluted conditions in a flow catalytic reactor with a continuous IR detection of products. The data, reported here, confirm that 3% Ru/Al2 O3 is an excellent catalyst for CO2 methanation (96% methane yield with no CO coproduction at 573 K at 15, 000 h −1 GHSV in excess hydrogen). The performance is better than that of Ni/Al2 O3 catalyst. The reaction orders over both catalysts with respect to both hydrogen and CO2 were determined over conditioned catalysts. A conditioning of the Ru/Al2 O3 catalyst by reactant gas stream was found to be needed and more effective than conditioning in hydrogen, possibly because water vapour formed during methanation reaction will react to remove chlorine impurities from catalyst surface Conditioned Ru/Al2 O3 catalyst was found to retain stable high activity after different shut-down and start-up procedures, thus being possibly applicable in intermittent conditions. Highlights: 3% Ru/Al2 O3 is an excellent catalyst for CO2 methanation. H2 and CO2 reaction orders were determined over Ni and Ru conditioned catalysts. 3% Ru/Al2 O3 requires on stream conditioning to reach full activity. conditioning is associated to cleaning chlorine impurities from the surface. conditioned Ru/Al2 O3 catalyst retains stable high activity after different cycles.